A Qualitative Analysis of Action Pack 5 - Teacher’s Book in Light of Skierso’s Evaluation Checklist - Kfair, Qasem; Smadi, Oqla (DIRASAT: EDUCATIONAL SCIENCES, 2017)
This paper aims at analyzing the content of Action Pack 5-Teacher’s Book according to a collection of criteria selected from Skierso’s Evaluation Checklist. The qualitative content analysis is used to examine and analyze the content of this Teacher’s Book to determine to what extent it meets the needs of English teachers in Jordan. To achieve the purpose of this paper, seven criteria from Skierso’s Evaluation Checklist concerning some aspects of the methodological and pedagogical guidance of the teacher’s manual have been selected. The findings of this paper have revealed that Action Pack 5- Teacher’s Book provides guidance for the teacher on the teaching of language items and skills. It also provides teachers with effective material for training the students in the listening, speaking, reading and writing skills in a way which integrates all these four skills Moreover, Action Pack 5- Teacher’s Book provides teachers with varied teaching aids that are very beneficial.